Government accountability and improved social welfare: A literature review - Suhu, Bakri La; Agusmawanda, Agusmawanda; Ibrahim, Abdul Halil Hi.; Pora, Rasid; Radjak, Darwin Abd (The International tax journal, 2025)
Government accountability plays a fundamental role in improving social welfare. Through the implementation of the principles of transparency and accountability, the government can build public trust and encourage citizen participation in various development programmes. Good accountability also plays a role in reducing corruption and abuse of authority, thus ensuring that public funds are used efficiently for the benefit of the community. With optimal resource management, more allocations can be made to important sectors such as education, health, and infrastructure, which directly impact the improvement of people's quality of life. In addition, continuous oversight through the active participation of civil society and the mass media ensures that the government continues to operate with integrity, implementing policies that are more effective and have a positive impact on social welfare. Therefore, synergy between the government and the community is the key to achieving and maintaining sustainable and equitable social welfare.